1997
DOI: 10.1038/sj.bjp.0701520
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the role of α2‐adrenoceptor subtypes in the antinociceptive, sedative and hypothermic action of dexmedetomidine in transgenic mice

Abstract: 1 The role of a 2 -adrenoceptor (AR) subtypes in the modulation of acute nociception, motor behaviour and body temperature, has been investigated by determining the activity of the a 2 AR selective agonist dexmedetomidine (Dex) in mice devoid of individual a 2 AR subtypes through either a point (a 2A ) or null (a 2B /a 2C ) mutation (`knock-out').2 In a rodent model of acute thermal nociception, the mouse tail immersion test, Dex, in wild type (WT) control animals, produced a dose-dependent increase in the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
139
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(161 citation statements)
references
References 38 publications
16
139
1
2
Order By: Relevance
“…Furthermore, we found that the anti-allodynic and the antinociceptive eects of dexmedetomidine were intact in a 2B and a 2C AR, but absent in the a 2A AR mutant mice. Our results agree with previous reports showing that the antinociceptive eect of dexmedetomidine in the hot-plate and tail-¯ick tests is mediated via an activation of a 2A AR (Lakhlani et al, 1997;Hunter et al, 1997;Stone et al, 1997) and indicate that the same receptor comes into play under both acute and persistent pain conditions.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Furthermore, we found that the anti-allodynic and the antinociceptive eects of dexmedetomidine were intact in a 2B and a 2C AR, but absent in the a 2A AR mutant mice. Our results agree with previous reports showing that the antinociceptive eect of dexmedetomidine in the hot-plate and tail-¯ick tests is mediated via an activation of a 2A AR (Lakhlani et al, 1997;Hunter et al, 1997;Stone et al, 1997) and indicate that the same receptor comes into play under both acute and persistent pain conditions.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies suggested that the a 2A subtype mediates the antinociceptive eect of a 2 AR agonists in acute models of pain (Hunter et al, 1997;Lakhlani et al, 1997;Stone et al, 1997). However, because a 2 AR expression may be altered after nerve injury (Cho et al, 1997;Fareed et al, 1997;Birder & Perl, 1999;Stone et al, 1999;Shi et al, 2000), it is possible that the action of dexmedetomidine is altered by nerve injury or that the a 2 AR receptor subtype that is responsible for its antinociceptive eect is dierent.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…The almost totally abolished startle reflex of WT mice after Dex 10 and especially 30 mg/kg was likely due to its sedative effect. The sedation elicited by a 2 -AR agonists is mainly mediated through activation of a 2A -AR, and has previously been shown to be attenuated, but not totally absent in mice lacking functional a 2A -AR (Hunter et al, 1997;Lakhlani et al, 1997;Lähdesmäki et al, 2003). The smallest Dex dose, 3 mg/ kg, is not, however, sedative in mice (Hunter et al, 1997), but still effectively reduced startle in WT mice.…”
Section: Discussionmentioning
confidence: 96%
“…Gene manipulation in mice reveals which receptor subtype elicits a particular physiological or behavioral response in vivo, and has revealed the crucial role of the ␣ 2A -adrenergic receptor (␣ 2A -AR) subtype in mediating the ability of ␣ 2 -agonists to elicit hypotension (1-3), sedation (4), anesthetic sparing and analgesia (4,5), hypothermia (6,7), synergism with opiates in the antinociceptive response (5), and enhancement of working memory in mice (10). The latter finding suggests that the beneficial effects of guanfacine in working memory in primates (11) and in the enhancement of attentional focus in patients with attention deficit hyperactivity disorder (12) is attributable to ␣ 2A -AR actions.…”
mentioning
confidence: 99%